Avoidant Personality Traits and Their Impact on Communication Effectiveness Among Students on Campus - Merdeka, Amellia Sukma; Nuruzzaman, M. (Journal Research of Social Science, Economics, and Management, 2026)
Interpersonal communication is a crucial element in students' lives; however, some students still face challenges in communicating effectively within the campus environment. The growing discussion of avoidant behaviour among young people, high levels of social anxiety, and low levels of self-disclosure indicate the existence of issues in students' interpersonal interactions. This research aims to identify the characteristics of avoidant behaviour among students, analyse the effectiveness of communication among students, and identify the factors contributing to the development of such behaviour in an academic context. This research employs a descriptive qualitative approach, with students selected through purposive sampling as informants. Data were collected through semi-structured interviews and analysed using thematic analysis with reference to Communication Effectiveness Theory. The results indicate that students with avoidant tendencies tend to avoid conflict, limit the intensity of communication, maintain emotional distance, and communicate only when necessary. Communication effectiveness is not yet fully optimised, as miscommunication, limited feedback, and barriers to self-disclosure are still observed; thus, avoidant behaviour is strongly linked to the dynamics of interpersonal communication effectiveness among students in the campus environment.